Ewing sarcoma: methods and protocols - Cidre-Aranaz, Florencia; Grünewald, Thomas G. P. (Springer US, 2021)
Germline Variation and Somatic Alterations in Ewing Sarcoma -- Western Blot Analysis in Ewing Sarcoma -- Tissue Preservation and FFPE Samples: Optimized Nucleic Acids Isolation in Ewing Sarcoma -- Liquid Biopsies in Ewing Sarcoma -- (Immuno-)histological Analysis of Ewing Sarcoma -- Molecular Approaches to Diagnosis In Ewing Sarcoma: Fluorescence in situ hybridization (FISH) -- Molecular Approaches to Diagnosis in Ewing Sarcoma: RT-PCR -- Molecular Approaches to Diagnosis in Ewing Sarcoma: Targeted RNA Sequencing -- Ewing-specific (re)expression Models -- Analysis of Regulatory Sequences by Dual-luciferase Reporter Assays in Ewing Sarcoma -- Proliferation Assessment by Trypan Blue Exclusion in Ewing Sarcoma -- Drug Screening by Resazurin Colorimetry in Ewing Sarcoma -- Analysis of Migration and Invasion in Ewing Sarcoma -- Genetically Engineered Mouse Model in Ewing Sarcoma -- Tumor Growth Analysis of Ewing Sarcoma Cell Lines Using Subcutaneous Xenografts in Mice -- Metastasis Assessment in Ewing Sarcoma Using Orthotopic Xenografts -- Orthotopic Implants in Mice -- Ewing Sarcoma PDX Models -- Using Zebrafish Larvae as a Xenotransplantation Model to Study Ewing Sarcoma -- Main Repositories and Databases used in Ewing Sarcoma Research -- Chromatin Immunoprecipitation Followed by Next-Generation Sequencing (ChIP-seq) Analysis in Ewing Sarcoma -- Epigenetic Analysis in Ewing Sarcoma -- Systems Biology Analysis for Ewing Sarcoma.